ANALISA VALUASI EMITEN KARYA LISTED IDX - ., M Aditya Ananda (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2021)
ABSTRACT This study aims to analyze the stock valuation of construction issuers, especially BUMN Karya using data for the first quarter – third quarter of 2020 obtained from financial statements. The ratio used is the valuation ratio such as Price to Book Value and Price to Earning to Share. The solvency ratio used is the Debt to Equity Ratio and the market cap value. The three construction issuers that are the focus of the analysis are PT Waskita Karya (WSKT), Tbk, PT Wijaya Karya, Tbk (WIKA) and PT. Pembangunan Perumahan, Tbk (PTPP). From the results of the analysis obtained in the third quarter of 2020, WSKT has a value of PBV 0.84, PER -7.56, DER 3.87 with a Market Cap of 19.9T. WIKA has a value of PBV 1.00, PER 320.79, DER 2.80 and Market Cap 16.1T. while PTPP, has PBV 0.66, PER 358.82, DER 2.79, Market Cap 9.4T. among the three issuers, WSKT has a negative value due to having a corrected profit in the third quarter of 2020. While the lowest PBV is owned by PTPP while the highest DER is owned by WSKT.